Kashmirobia, a new genus of flea beetles from the Oriental Region (Coleoptera: Chrysomelidae) - Konstantinov, A. S.; Prathapan, K. D. (Zootaxa, 2006)
A new genus, Kashmirobia, with the type species Aphthona hugeli Jacoby from the Oriental Region is described and illustrated. Comparative notes are provided. Host plant of K. hugeli is Euphorbia neriifolia L. (Euphorbiaceae).